an Analysis of Bank Soundness by Using the Risk Profile, Good Corporate Governance, Earning and Capital Methods for Registered Banks on the Indonesia Stock Exchange for the 2014-2016 Period: Analysis of Bank Soundness by Using the Risk Profile, Good Corporate Governance, Earning and Capital Methods for Registered Banks on the Indonesia Stock Exchange for the 2014-2016 Period - Afrialdy, Muhammad Rizqy (Jurnal Kompetitif Bisnis, 2020)
The health or financial and non-financial condition of a bank is in the interest of all parties concerned, including owners, bank management, government banks (Bank Indonesia) and users of bank services to evaluate the performance of banks in applying prudential principles, compliance with applicable regulations and risk management. A healthy bank is a bank that can maintain and maintain public trust, can carry out the intermediation function, can help smooth the payment system and can be used by the government in implementing various policies, especially monetary policy. By carrying out these functions, it is expected to be able to provide good services to the community and benefit the economy as a whole.